The Adoption of Internet Banking in a Developing Economy - Govender, Jeevarathnam P (Journal of Economics and Behavioral Studies, 2013)
The international world has witnessed significant developments in internet banking. This has presented opportunities to both banks and customers in the world of e-commerce. The adoption rate for internet banking in South Africa has been low, compared to other developing countries. With a reasonably well developed infrastructure, South Africa presents itself with great market potential for internet banking. Given this scenario, this paper examines the factors influencing the adoption of internet banking in South Africa. A survey was conducted using a sample of 400 consumers using a quantitative and descriptive design. The results indicate a relationship between the selected biographical variables and the adoption of internet banking. Perceived usefulness, an indicator of relative advantage was associated with the adoption of internet banking. Users considered internet banking to be less complex and less costly than non-users. It emerged that both users and non-users did not consider social influences as being a factor in the adoption of internet banking.